2007
DOI: 10.1074/jbc.m701997200
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated Endocytosis Involves Tyrosine Phosphorylation of Cortactin

Abstract: Efficient internalization of cell surface receptors requires actin polymerization mediated by Arp2/3 complex and cortactin, a prominent substrate of the protein-tyrosine kinase Src. However, the significance of cortactin tyrosine phosphorylation in endocytosis is unknown. We found that overexpression of a cortactin mutant deficient in tyrosine phosphorylation decreased transferrin uptake. Suppression of cortactin expression by RNA interference also reduced transferrin internalization. Such inhibition was effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 54 publications
1
55
1
Order By: Relevance
“…In this process, dynamin 2 could also affect the activity of the Arp2/3 complex indirectly through cortactin Krueger et al, 2003). Of note, recent findings have shown that Src-dependent phosphorylation of cortactin enhances its affinity for dynamin-2 more than threefold (Zhu et al, 2007), suggesting a possible molecular basis for the stimulatory effect of cortactin phosphorylation by SFK in invadopodia formation. An interesting twist might be provided by a recent report suggesting that cortactin functions in regulating matrix metalloprotease secretion at invadopodia (Clark et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this process, dynamin 2 could also affect the activity of the Arp2/3 complex indirectly through cortactin Krueger et al, 2003). Of note, recent findings have shown that Src-dependent phosphorylation of cortactin enhances its affinity for dynamin-2 more than threefold (Zhu et al, 2007), suggesting a possible molecular basis for the stimulatory effect of cortactin phosphorylation by SFK in invadopodia formation. An interesting twist might be provided by a recent report suggesting that cortactin functions in regulating matrix metalloprotease secretion at invadopodia (Clark et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous observations that Src kinase can regulate internalization and release of TfR1 containing clathrin-coated pits by tyrosine phosphorylation of Dyn2 and its actin binding partner cortactin (10,11), it is possible that several potential layers of regulation exist that mediate the internalization and trafficking of this trophic receptor.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies by us and others (10,11) have suggested that the binding of the Tf ligand leads to the activation of Src kinase, which in turn promotes phosphorylation of specific components of the endocytic machinery such as dynamin 2 (Dyn2) and its actin-associated binding partner cortactin (12)(13)(14)(15)(16). The Src-mediated phosphorylation event of these specific endocytic components appears to be essential for efficient assembly and scission of clathrin-coated pits that are utilized to internalize this receptor-ligand complex.…”
mentioning
confidence: 99%
“…There is increasing evidence supporting that cortactin is a prominent substrate of Src-protein-tyrosine kinase (18,26), and that tyrosine phosphorylation of cortactin occurs frequently in response to various extracellular stimuli, including growth factors, bacterially-mediated phagocytosis, cell shrinkage and membrane injury. Although studies have found that the introduction of a mutant cortactin deficient in tyrosine phosphorylation impairs cell motility, tumor invasion, invadopodia, and podosome formation (18,20,27,28), and that cortactin plays important roles in tumor growth, there have been few reports on the role of cortactin regulation in tumors by epigenetic modification.…”
Section: Discussionmentioning
confidence: 99%